The impact of bush forming system on monoterpene composition of grapes - Tkachenko , O. B.; Pashkovskyi , O. I.; Kovana, O. O.; Yurchenko , Ye. M. (Scientific Progress & Innovations, 2019)
The aim of the article is to study the dependence of accumulating monoterpenes in grape berries of Aromatnyi and Zagrey varieties on the choice of bush forming systems. The methods of research. The scheme of the experiment included 4 systems of stem boundary formations that differed in height (40, 80, 120, 160 cm) and the method of keeping one-year growth (vertical or non-positioned). The temperature of bunches during grape ripening period was measured, using a contactless pyrometer. The concentration of monoterpenes in grapes was determined by means of steam distillation and gas chromatography. The results of the study. Studying the temperature regime of bunches during grape ripening period, we established that bunches of low-stemmed bushes were characterized by the highest index value during the day, while the bunches of high-stemmed bushes – by the lowest one. The expediency of high-stemmed bush formations of Aromatnyi variety for realizing the grape aromatic potential has been determined. The using of this viticulture practice enabled to obtain raw product with the highest concentration of free and bound fraction of monoterpenes. Linalool was identified as the main component in both fractions. Similarly, for Zagrey variety, during bush forming on low stems, the highest accumulation of the bound fraction of monoterpenes was recorded. Geraniol, linalool and beta-citronellol prevailed in separate components of this fraction. Using the methods of correlation and regression analysis the connection between the total accumulation of monoterpenes’ bound fraction and its separate components, linalool (Aromatnyi variety) and beta-citronellol (Zagrey variety) and the temperature of bunches during the ripening period was established. The elements of scientific novelty. For the first time in Ukraine, the impact of bush forming systems on grape monoterpenes composition has been studied. The expediency of differentiated choosing viticulture practices in the context of varieties for the realization of their aromatic potential has been established. Practical significance. The results can be used in industrial viticulture when creating new plantations of Aromatnyi and Zagrey varieties in order to obtain high-quality raw product for winemaking.